Fecal microbiota transplantation from chronic unpredictable mild stress mice donors affects anxiety-like and depression-like behavior in recipient mice via the gut microbiota-inflammation-brain axis. (3rd September 2019) - Li, Nannan; Wang, Qi; Wang, Yan; Sun, Anji; Lin, Yiwei; Jin, Ye; Li, Xiaobai
Abstract: Recent studies have demonstrated that there are significant changes in the gut microbiota (GM) of humans with depression and animal models of depression and chronic stress. In our present study, we determined whether an alteration in GM is a decisive factor in anxiety-like and depression-like behavior and its impact on brain neurochemistry. An antibiotic cocktail was used to deplete the GM of mice before they were colonized, via fecal microbiota transplantation (FMT), by the GM of control mice or mice that had been exposed to chronic unpredictable mild stress (CUMS donors). The CUMS-donor group of mice and the mice that were colonized by their microbiota (the CUMS-recipient group) both showed higher levels of anxiety- and depression-like behavior compared to the controls. The GM community of the CUMS-donor and CUMS-recipient was distinctively different from the controls, with the CUMS group characterized by a lower relative abundance of Lactobacillus and a higher relative abundance of Akkermansia . Interestingly, FMT affected both behavior and neuroinflammation. Mice given the CUMS microbiota had significant elevations of interferon-γ (IFN-γ) and the tumor necrosis factor-alpha (TNF-α) in the hippocampus, which were accompanied by upregulated indoleamine 2, 3-dioxygenase 1 (IDO1) in the hippocampus. These results suggest that GM modulates pro-inflammatory cytokines in the hippocampus through dysfunctional microbiota–gut–brain axis, exacerbating anxiety- and depression-like phenotypes. Key Points: Chronic unpredictable mild stress increased anxiety- and depression-like behavior in mice. Mice colonized with gut microbiota (GM) from stressed mice showed similar behaviors. The GM composition of the donor and recipient mice was also comparable. Their relative pattern of two bacteria has been tied to neuroinflammatory activity. The results suggest a link between GM, brain function, and anxiety and depression.